Moral values and instrinsic elements depicted in the novel entitled black notice by patricia cornwell - Novida, Nelly; Tahrun, Tahrun; Sari, Artanti Puspita (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Great value and culture of Indonesian people that very popular around the world. The highly complex conflict in Indonesia is generally extremely concerning, particularly the normative downturn. This same real dilemma is also taking place in the world of schooling. So this study aimed to reveal the moral value and instrinsic elements form the novel Black Notice by Patricia Cornwell relate to people from different environment by interview. The data of the research were gained through triangulation technique taken from novel, book review and interview which are analysed with desrcriptive qualitatively afterwards,and describe the condition and relation which are held and process still going. The results of the study found that certain moral values and intrinsic features include the novel Black Notice by Patricia Cornwell using the Social And cultural Historical Technique and the Biographical Framework.